Integrating TAM, Trust and Perceived Risk Factors on Emerging-Market Consumers’ Attitude Towards Shopping for Muslim Fashion Online - Sari, Ratna Deli; Hersusetiyati; Ekaputra, Adriansyah Ekaputra; Ihwani, Najmi (Sinergi International Journal of Management and Business, 2024)
This study aims to explore the factors affecting consumer attitudes towards using online shopping platforms, especially for purchasing muslim fashion online . The research is grounded in The Technology Acceptance Model (TAM) by Davis (1986), and examines variables such as perceived usefulness and perceived ease-of-use, as well as trust and perceived risk, in relation to consumer attitudes towards online shopping. The study employs a survey method to collect data and information for analysis. Causal analysis is conducted using Linear Regression PROCESS version 3.4 with the help of SPSS version 24. The sample consists of 100 consumers who have previously bought Muslim fashion online, randomly selected from Bandung. The findings reveal that perceived usefulness, perceived ease-of-use, trust, and perceived risk significantly impact consumer attitudes towards repeated online shopping.